Stimulation Parameters Used During Repetitive Transcranial Magnetic Stimulation for Motor Recovery and Corticospinal Excitability Modulation in SCI: A Scoping Review - Brihmat, Nabila; Allexandre, Didier; Saleh, Soha; Zhong, Jian; Yue, Guang H.; Forrest, Gail F. (Frontiers in Human Neuroscience, 2022)
There is a growing interest in non-invasive stimulation interventions as treatment strategies to improve functional outcomes and recovery after spinal cord injury (SCI). Repetitive transcranial magnetic stimulation (rTMS) is a neuromodulatory intervention which has the potential to reinforce the residual spinal and supraspinal pathways and to induce plasticity. Recent reviews have highlighted the therapeutic potential and the beneficial effects of rTMS on motor function, spasticity, and corticospinal excitability modulation in SCI individuals. For this scoping review, we focus on the stimulation parameters used in rTMS protocols. We extracted the rTMS parameters from 20 published rTMS studies involving SCI individuals and were able to infer preliminary associations between specific parameters and the effects observed. Future investigations will need to consider timing, intervention duration and dosage (in terms of number of sessions and number of pulses) depending on the stage, the level, and the severity of the injury. There is a need for more real vs sham rTMS studies, reporting similar designs with sufficient information for replication, to achieve a significant level of evidence regarding the use of rTMS in SCI.